„Pártoljátok az árvák és özvegyek ügyét”: A társadalmi gondoskodás felelőssége a zsidó-keresztény kultúrkörben - Mondovics, Napsugár (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2024)
The prophetic exhortation quoted in the title calls for the learning of correct moral values, the conscious choice and pursuit of values that determine almost all manifestations of the individual and the community. The values set as a model and passed on to the younger generations have a normative impact on the inner life of the community, on the coexistence of rich and poor, donors and recipients, citizens and recipients. In my study I seek for an answer to the question of how the idea of social care is expressed in principles, customs and legal institutions throughout the legal order of the Old and New Testament. My aim is to collect the universal values that can form the basis of the social safety net adapted to the times.